The effect of R & D and the control-ownership wedge on firm value: Evidence from Korean Chaebol Firms - Kang, Minjung; Kim, Sangil; Cho, Moon Kyung (Sustainability (Switzerland), 2019)
Cases have been reported in which research and development (R & D) investment, the core activity for a firm's sustainable growth, deteriorate rather than increase firm value. This study illuminates the cause of such cases in terms of the control-ownership wedge. How expensed and capitalized R & D affect firm value are examined separately for cases in which the wedge is high and low. In an analysis of Korean chaebol firms, when the wedge is high, significant negative relationships appear between expensed R & D and firm value, while no significant relationship appears between capitalized R & D and firm value. When the wedge is low, expensed R & D does not show any significant relationship with firm value, while capitalized R & D shows significant positive relationships with firm value. This confirms, first, that in cases of high wedge, suboptimal R & D decisions are made, in which the manager can discretionally determine investment targets or projects. Second, this indicates that even in cases of low wedge, the positive relationship between R & D and firm value does not appear in expensed R & D. This study suggests that investors and regulatory authorities should pay close attention to the initial stage of R & D in firms with high control-ownership wedges for sustainable economic growth.
Keywords: Capitalized research and development; Control-ownership wedge; Expensed research and development; Firm value; Research and development investments